STRATEGIC DEVELOPMENT OF UZBEKISTAN’S HIGHER EDUCATION SYSTEM IN THE CONTEXT OF DIGITAL TRANSFORMATION: A DEEP SWOT ANALYSIS BASED ON THE SYSTEMS APPROACH - Bulturov Jamshidbek; Sodirjonov Muhriddin (INTERNATIONAL CONFERENCE ON SCIENCE, INNOVATION AND GLOBAL DEVELOPMENT, 2026)
This article explores the strategic development of Uzbekistan’s higher education system in the era of digital transformation through a deep SWOT analysis based on the systems approach. In the context of the “New Uzbekistan” strategy and the “Digital Uzbekistan-2030” program, the strengths and weaknesses of the system, along with external opportunities and threats, are analyzed in detail. As a result, practical recommendations are provided for modernizing the higher education system according to the requirements of the digital age and enhancing its competitiveness.